EFFECTS OF BETA-BLOCKER METOPROLOL ON QUALITY OF LIFE IN ELDERLY PATIENTS WITH CHRONIC HEART FAILURE - I. V. Vologdina (Столичная издательская компания, 2015)
Aim. To study effect of cardioselective β-adrenoblocker metoprolol tartrate (in retarded formulation) on quality of life in elderly patients with chronic heart failure (CHF) of ischemic etiology.Material and methods. 78 patients with CHF class III (NYHA) were involved in the study. Patients were 81,6±0,25 y.o. in average. All patients had clinical signs of mild-to-moderate depressive disorders. Patients were split on 2 groups comparable in sex and age. Patients of the 1st group (n=43) received metoprolol tartrate (Egilok Retard), 50-100 mg/d additionally to standard therapy. Patients of the 2nd group (n=35) received only standard therapy. The somatic status was assessed before and after 1 and 3 months of therapy by clinical condition evaluated scale (CCES), 6-minute walking test, left ventricular ejection fraction (Echocardiography) as well as mental status by special tests (SMSP, BDI, Hamilton scale, C.D.Spilberger-Y.L.Hanin scale) and qualities of life (MLHFQ, SF-36).Results. Reduction of CHF class from III to II was observed in 31 (76,7%) patients of the 1st group and in 23 (65,7%) patients of the 2nd group. Tolerability of Egilok Retard was good and there were not cessations because of side effects. In 3 months of therapy severity of the somatic status according to CCES reduced more significantly in the 1st group in comparison with the 2nd group (29,5 % vs 11,5 %, p <0,001). The exercise tolerance increased higher in the 1st group comparing with the 2nd one (34 % vs 17 %, respectively, p<0,001). The severity of depression reduced (according to SMSP, Hamilton scale) more significantly in the 1st group in comparison with this in the 2nd one. Quality of life also improved more significantly in the 1st group according to MLHFQ and SF-36 (physical functions, role physical functions, social function scales) at the end of therapy.Conclusion. Metoprolol tartrate (in retarded formulation) improves somatic and mental status as well as quality of life in elderly patients with CHF.